Exploring Activities Teachers Use to Develop Learners' Readiness in Grade R: A Holistic Development Perspective - Segooa, Mapule Yvonne (Indonesia Approach Education, 2024)
The study sought to explore the methods used by Grade R instructors to assess students' readiness to progress to Grade One. Typically, both indoor and outdoor play activities are utilised in the teaching and learning process, with a focus on readiness exercises to analyse the generated data. Thematic analysis was used in conjunction with observations and document analysis. The findings revealed that Grade R instructors employ various strategies to promote readiness, including continuous evaluation through observation and formal and informal activities. These activities are aligned with CAPS guidelines to ensure students are adequately prepared and engaged in their learning as they transition to first grade. Suitable recommendations were made based on the results of the study.